Study of the development of beach ecotourism based on sustainable local wisdom - Sinta Veronika Hutabarat; Indra Setiawan Hutabarat; Dicky Syahputra Lubis; Heni Wardina; Yusi Tri Utari Panggabean (Enrichment : Journal of Management, 2023)
Based on the results of research conducted related to the Study of The Development of Beach Ecotourism Based on Sustainable Local Wisdom in Central Tapanuli Regency in 2023. The research method used in this study is combined (Mixed Methodology) using quantitative and qualitative explanatory approaches. The data collection in this study was to use primary data and secondary data, where the determination of the number of respondents was able to represent the area of the study location. as many as 45 people. It is concluded based on the results of research that the locus of study is very worthy of being used as a tourism place because there are many supporting elements and has enormous economic potential.